Effect of NAA, GA, on growth, yield and quality of cluster bean, okra and cowpea in arid condition of south-western Rajasthan (Indian Journal of Arid Horticulture, 2020)
The field experiments were conducted on three different vegetable crops at College of Agriculture, Sumerpur (Rajasthan) during Kharif and Zaid season of 2018-19 continuously to study the effect of plant growth regulators (NAA, GA,) on growth, yield and quality of cluster bean [Cyamopsis tetragonoloba (L) Taub.], okra (Abelmoschus esculentus L.) and cowpea (Vigna unguiculata). The experiments were laid out in randomized block design with sixteen treatments in three replications. The treatment comprised of three levels of individual growth regulator of GA, and NAA (50, 100, 200 ppm) and their nine combinations. Results revealed that the all variables regarding vegetative and reproductive growth were influenced by different concentrations of the growth regulators. Growth regulators were less effective when applied individually as compared to their combined use however, performance of plants treated with individual PGR was better than the untreated plants. In cluster bean, among the different combination of treatments, T12 (GA, 100 ppm + NAA 200 ppm) registered the maximum number of pod cluster plant' (20.25), number of pods plant (344.71), marketable green pod yield (116.07 q ha''), highest net return of Rs.265207.50 ha with maximum B:C ratio of 3.23 as compared to rest of the treatment combinations. In okra T,, treatment (GA, 200 ppm and NAA 200 ppm) performed better than other treatments with the highest number of fruits plant (12.60), fruit length (10.90 cm), fresh weight of fruit (10.69 g), total fruit yield (67.34 q ha'') and net return of Rs. 132867.5 ha' with maximum B:C ratio of 2.74. Cowpea also performed better when medium dose of growth regulators (100 ppm GA, + 100 ppm NAA) were applied under T1, treatment with maximum pod yield plant (198.85 g), marketable green pod yield (99.64 q ha), highest net return Rs. 133394.00 ha with maximum B:C ratio of 3.81 as compared to rest of the treatments.
Keywords: GA; Napthalene-acetic-acid; morpho-physiological traits; plant growth regulator